Hubungan antara Psychological Well Being dan Kepuasan Kerja pada Karyawan di Kantor X - Joy Krismarwaty Tasema (Politeknik Negeri Ambon, 2018)
This research aims to know the relationship between psychological well being and job satisfaction by using quantitative methods with the technique of correlation of Product Moment of Carl Pearson. The hypothesis in this study is a positive correlation between psychological well being and job satisfaction on employees in Kantor X . Measuring instrument used in this study is psychological well being Scale Ryff’s (1989) with the reliability test results amounted to 0,915. The second scale of job satisfaction by Brayfield and Rothe (1951) with the reliability test results amounted to 0,825. On average psychological well being variable subject obtain score 81,90 who belongs in the category of variable height, and job satisfaction of the average score obtained 49,25 the subject belongs in the category. Correlation analysis of product moment in earned value r = 0.632 (p < 0.05); thus there is a relationship between significant positive relationship between psychological well being and job satisfaction on employees in Kantor X.